Reformatorskie działania w edukacji wczesnoszkolnej uczniów z niepełnosprawnością – „druzgocące fakty dokonane” czy postęp? - Sławomira Sadowska (Problemy Wczesnej Edukacji)
Reforming actions after the political change in 1989 brought new interpretations of work to the first stage of education and changes in the existing qualifications of teachers working in grades I–III of special schools. The read standards of work from the field of documents from the Ministry of Education stand in opposition to the expanse of positions expressed by scientific circles, while the first ones imprint their explicit stigma on the teacher conceptualizations of work in the first educational stage. The concept of work in classes I–III, developed on the basis of special pedagogy, despite the fact that the reformed school did not question its basic assumptions, is no longer an axis of thought in working with pupils with disabilities.